Scale-up from shake flasks to pilot-scale production of the plant growth-promoting bacterium Azospirillum brasilense for preparing a liquid inoculant formulation (2013)
Azospirillum brasilense has industrial significance as a growth promoter in plants of commercial interest -- However, there is no report in the literature disclosing a liquid product produced in pilot-scale bioreactors and is able to be stored at room temperature for more than 2 years -- The aim of this work was to scale up a process from a shake flask to a 10- L lab-scale and 1,000-L pilot-scale bioreactor for the production of plant growth-promoting bacterium A -- brasilense for a liquid inoculant formulation -- Furthermore, this work aimed to determine the shelf life of the liquid formulation stored at room temperature and to increase maize crops yield in greenhouses -- Under a constant oxygen mass transfer coefficient (KLa), a fermentation process was successfully scaled up from shake flasks to 10- and 1,000-L bioreactors -- A concentration ranging from 3.5 to 7.5×108 CFU/mL was obtained in shake flasks and bioreactors, and after 2 years stored at room temperature, the liquid formulation showed one order of magnitude decrease -- Applications of the cultured bacteria in maize yields resulted in increases of up to 95 % in corncobs and 70 % in aboveground biomass